2016
DOI: 10.1093/mnras/stw2556
|View full text |Cite
|
Sign up to set email alerts
|

Erasing the Milky Way: new cleaning technique applied to GBT intensity mapping data

Abstract: We present the first application of a new foreground removal pipeline to the current leading HI intensity mapping dataset, obtained by the Green Bank Telescope (GBT). We study the 15hr and 1hr field data of the GBT observations previously presented in Masui et al. (2013) and Switzer et al. (2013), covering about 41 square degrees at 0.6 < z < 1.0, for which cross-correlations may be measured with the galaxy distribution of the WiggleZ Dark Energy Survey. In the presented pipeline, we subtract the Galactic fore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 36 publications
(40 reference statements)
3
84
0
Order By: Relevance
“…Modelling and addressing the foreground removal problem with dedicated simulations is a very active area of research (see, for example, (Wolz et al 2014;Shaw et al 2015;Wolz et al 2017)). The conclusion of such work is that component separation methods can in principle be used to remove these foregrounds.…”
Section: Foregroundsmentioning
confidence: 99%
“…Modelling and addressing the foreground removal problem with dedicated simulations is a very active area of research (see, for example, (Wolz et al 2014;Shaw et al 2015;Wolz et al 2017)). The conclusion of such work is that component separation methods can in principle be used to remove these foregrounds.…”
Section: Foregroundsmentioning
confidence: 99%
“…Further blind component separation methods include Generalalized Morphological Component Analysis (GMCA) (Chapman et al 2013) and Generalized Internal Linear Combination (GnILC) (Remazeilles et al 2011). For this work we examine the FAS-TICA method (Hyvärinen 1999;Chapman et al 2012;Wolz et al 2014Wolz et al , 2017, which we describe in the following section. Alonso et al (2015) found there to be very little distinction between a PCA and ICA approach to foreground cleaning, so our choice of FASTICA as a foreground removal process should not affect the generality of our conclusions.…”
Section: Foreground Removalmentioning
confidence: 99%
“…Excepting the P TT monopole, all statistics and multipoles produce a satisfactory value of the χ 2 statistic with χ 2 /dof ∼ 1 for scales k < 0.2 h Mpc −1 . Current cross-correlation analyses of radio intensity mapping and galaxy surveys have produced ∼ 3-σ detections of the cross-power spectrum amplitude, and corresponding constraints on the neutral hydrogen density at intermediate redshifts (Chang et al 2010;Masui et al 2013;Wolz et al 2017;Anderson et al 2018). Analysis of the auto-power spectrum of intensity Figure 2.…”
Section: Simulation Testmentioning
confidence: 99%